Digital news media coverage of Jakarta regional head election 2017 - Anggoro, Ayub Dwi
Previous research on the construction of media reality concluded that in playing the role of politics to influence the public, it was done with a scheme to manipulate the context, cognition and text of the news. The media owner refuses to be blamed if a news error occurs because it would disrupt his business. The development of the media industry today has created new problems. The competition in the media industry is no longer for business purposes but involved of political issues. The current situation occurs due to the active participation of businessmen in political parties. News produced by the media is influenced by the ideological value of the media owner. This study is focusing on analysing the news published online by mediaindonesia.com and okezone.com. The purpose of this study is to identify the ideological perspective, analyse issues exposed in their published news, and evaluate the publication strategies used by the two media regarding the texts, cognition and context. This research uses a qualitative approach supported by quantitative analysis. The analysis covers the headline news dcl ivered by two online media, namely, mediaindonesia.com and okezone.com, between the period of October 2016 and April 2017 using the Critical Discourse Analysis method, namely the Teun A. Van Dijk model. In terms of the quantitative data, the researcher employs SPSS for the descriptive analysis of the 1541 proclamations published by both mediaindonesia.com and okezone.com. The process of critical discourse analysis classifies ideology through positive and negative news images in the categories of issues raised by the media. The findings showed that the frequency of news reports by mediaindonesia.com for candidates of Governor Agus and Sylviana yielded 183 or (I8.5%) publications, Basuki Tjahaja Pumama and Djarot Saeful Hidayat had the highest news headline frequency with a total of 564 or (56.9%) coverages, while Anies and Sandiaga reached 244 or (24.6%) publications. Based on the news produced by okezone.com, positive image attached to its published news amounted to 285 or (51.8%) from tbe total of the produced articles. The positive news framing was directed at the pair of Anies and Sandiaga. For the negative issues of 67 news (12.2%) of the total were aimed at Basuki and Djarot, while the neutral news reputation produced 198 news (36%) of the total coverage. Mediaindonesia.com confirms that Basuki and Djarot have high number of supports among politicians and artists. Okezone.com showed that Anies and Sandiaga received the highest support from the community. It can be concluded that the political news coverage scheme is an attempt to build the reputation or tbe candidate supported by the media. In the extension of the Teun Van Dijk's concept, ideology must be made into a dimension to carry out the analysis of text, cognition, and Context. Ideology is an independent unit that must be separated because ideology determines the direction of the news in its text, cognition, and context.